Parental Participation-Based Portfolio Assessment during Covid-19 Pandemic - Mahmudah Mahmudah; Muh Bashar Kapi; Muslimah Muslimah (Bulletin of Science Education, 2021)
The purpose of this study is to identify parental participation in guiding children’s learning at home During the covid-19 pandemi online. This research uses a descriptive qualitative approach, which describes theoretically through the method of tracing the relevance of this research. The results of the study shows that parental participation in carrying out portofolio assessments During the covid-19 pandemic play a very important role because learning during the pandemic requires parents to accompany online learning that is carried out during the pandemic, aspecially at elementay level students. The parents’ participation based portfolio assessment is appropriate to be implemented in teaching and learning process. Keywords: Portfolio Assessment, Assessment During Covid-19, Parental Participation Assessment